2019
DOI: 10.1101/552240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary dynamics determines adaptation to inactivation of an essential gene

Abstract: Genetic inactivation of essential genes creates an evolutionary scenario distinct from escape from drug inhibition, but the mechanisms of microbe adaptations in such cases remain unknown. Here we inactivate E. coli dihydrofolate reductase (DHFR) by introducing D27G,N,F chromosomal mutations in a key catalytic residue with subsequent adaptation by serial dilutions. The partial reversal G27->C occurred in three evolutionary trajectories. Conversely, in one trajectory for D27G and in all trajectories for D27F,N s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…Kwon et al (Kwon et al, 2010) have shown that inhibition of intracellular DHFR with very high concentration of TMP (6μg/ml) incurs large metabolic changes in the cell, with drop in glycine, methionine, purines and thymine levels. Similar data have been reported for engineered E. coli cells containing inactive mutants of DHFR (Rodrigues and Shakhnovich, 2019). However, as discussed in the previous section ( Figure 2E), we found that cells treated with high concentrations of TMP were phenotypically (with regard to cell length) very different than those treated with sub lethal concentrations.…”
Section: Filamentous Strains Have Imbalance Between Dttp and Other Desupporting
confidence: 91%
“…Kwon et al (Kwon et al, 2010) have shown that inhibition of intracellular DHFR with very high concentration of TMP (6μg/ml) incurs large metabolic changes in the cell, with drop in glycine, methionine, purines and thymine levels. Similar data have been reported for engineered E. coli cells containing inactive mutants of DHFR (Rodrigues and Shakhnovich, 2019). However, as discussed in the previous section ( Figure 2E), we found that cells treated with high concentrations of TMP were phenotypically (with regard to cell length) very different than those treated with sub lethal concentrations.…”
Section: Filamentous Strains Have Imbalance Between Dttp and Other Desupporting
confidence: 91%